2016
DOI: 10.1097/sap.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

Getting a Valid Survey Response From 662 Plastic Surgeons in the 21st Century

Abstract: Despite the convenience and low initial cost of web-based surveys, this generated the lowest response. We obtained statistically significant response rates (79% and 84%) only by using postal mail with monetary incentives and reminders. The inclusion of a $1 bill represented the greatest value and cost-effective survey method, based on cost per response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 6 publications
2
20
0
1
Order By: Relevance
“…The frequencies and associations reported are based on the responses of 210 surgeons (24%) out of a total of 952 surveyed surgeons. This response rate is comparable to reported mean response rates for physicians completing Web‐based surveys . Nonetheless, a large proportion of the sample was not included in the analysis, warranting discussion of responder and nonresponder bias.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The frequencies and associations reported are based on the responses of 210 surgeons (24%) out of a total of 952 surveyed surgeons. This response rate is comparable to reported mean response rates for physicians completing Web‐based surveys . Nonetheless, a large proportion of the sample was not included in the analysis, warranting discussion of responder and nonresponder bias.…”
Section: Discussionsupporting
confidence: 54%
“…This response rate is comparable to reported mean response rates for physicians completing Web-based surveys. 21,22 Nonetheless, a large proportion of the sample was not included in the analysis, warranting discussion of responder and nonresponder bias. No incentives or monetary or material prizes were offered to responders; a brief message in the body of the survey e-mail stated that participation in the survey would ultimately help "improve the design and utility of the ACS TPUSC" only.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Email surveys without financial incentives are associated with lower response rates among surgeons. 29 However, an assessment of potential nonresponse bias, as described by Halbesleben and Whitman, 9 showed that this was likely not large enough to alter the study conclusions, as late responders did not significantly differ from early responders on demographic characteristics or questionnaire items. Because late responders can serve as proxies for nonresponders, this implies that the results would not be substantially altered and are therefore generalizable to a broader audience.…”
Section: Limitationsmentioning
confidence: 98%
“…22 There is no doubt that a higher response rate would enhance the validity of the study, and consequently efforts have been made to identify strategies to encourage greater participation. [22][23][24][25][26] Although shorter surveys, repeated approaches and monetary incentives have yielded some benefits in the past, they have not been shown to consistently improve response rates among physicians. [22][23][24]26 The reason for the considerable variation in response rates from the 11.9% of plastic surgery residents to 42.8% of orthopedic residents is likely to be multifactorial.…”
Section: Limitationsmentioning
confidence: 99%
“…[22][23][24][25][26] Although shorter surveys, repeated approaches and monetary incentives have yielded some benefits in the past, they have not been shown to consistently improve response rates among physicians. [22][23][24]26 The reason for the considerable variation in response rates from the 11.9% of plastic surgery residents to 42.8% of orthopedic residents is likely to be multifactorial. How enthusiastically program directors and professional associations encouraged their residents to participate in the study will doubtless have played a part, but it must also be considered that those responding to this type of questionnaire may be a self-selecting group.…”
Section: Limitationsmentioning
confidence: 99%